Balongcabe Fresh (B-Fresh): An Effort to Improve the Economy of The Balongcabe Community Through Processing Soybean Agricultural Products - Zahro, Indah Fajrotuz; Inayati, Ummi; Aziz, M. Abdul; Herwanto, Dedy; Athoilah, M. Sya’ban (Academia Publication, 2025)
Balongcabe Village, Kedungadem, Bojonegoro has potential in the agricultural sector. Soybean is one of the commodities that many farmers grow in the dry season. Training on processing soybean agricultural products into soy milk aims to help improve the community's economy, because processed agricultural products will have a higher selling value than being sold raw. This service is carried out using the Asset Based Communities Development (ABCD) method with the stages of inculturation, discovery, design, define, and reflection. This training was carried out because farmers who previously only sold soybeans raw so they could process the soybeans into soy milk. The implementation of the training began with the presenters explaining the material for processing soybeans into soy milk and then practicing together on making soy milk, then packaging and marketing materials for soy milk. This training produced soy milk products with the B-Fresh brand (Balongcabe Fresh) in the hope of having good and profitable prospects as a small home industry to improve the economy of the people of Balongcabe village.